ETIKA PENGGELAPAN PAJAK: SURVEI ANTAR GENERASI PADA WAJIB PAJAK NON KARYAWAN DI INDONESIA - Josephine Kurniawati Tjahjono; Renna Magdalena (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
This study aimed to determine the ethics of tax evasion among non-employee individual taxpayers in Indonesia and classify the survey results into four generations: Baby Boomers, X, Millennials, and Z. For our investigation on the ethics of tax evasion, we employed the McGee questionnaire as a measuring instrument. This measuring instrument has been utilized in studies of a comparable nature in Spanish, Portuguese, Russian, and Turkish, among other languages and countries. This is the first investigation conducted in Indonesia. Individual non-employee taxpayers in Indonesia will not commit tax evasion if they believe the government has allocated public funds appropriately and if the current political and tax systems are perceived as ineffective or corrupt. The results indicate that Indonesian taxpayers tend not to engage in tax evasion for personal gain. In order to improve tax ethics and reduce tax evasion, it is necessary to increase the taxpayer's trust in the government, specifically by allocating tax funds efficiently and fostering public transparency.